Sedative and hemodynamic response of dexmedetomidine in critically ill South Indian population - Muthalu, Arunkumar; Asokan, Arthi; Ananthy, Vimala (Asian Journal of Medical Sciences, 2024)
Background: Dexmedetomidine is a selective alpha-2-adrenoceptor agonist. It exerts both sedative and analgesic effects through mechanisms different from those of other sedatives. The safety and efficacy of dexmedetomidine are altered by various factors. Aims and Objectives: This study aims at identifying the various factors that will affect the sedative and hemodynamic responses of dexmedetomidine in seriously ill patients. Materials and Methods: A continuous infusion of dexmedetomidine (0.2–0.7 μg/kg/h) was administered to intensive care unit patients who needed sedation. We investigated the safety and effectiveness of administering dexmedetomidine between responders and non-responders over a short (≤24 h) and lengthy (>24 h) period. Results: A total of 84 patients were analyzed who received dexmedetomidine. The longest possible duration of dexmedetomidine administration was 24.7 days and 7.8 days, respectively. Compared to the first 24 h, the number of patients who needed more sedatives or analgesics was not increasing beyond that time. In the first 24 h and after the first 24 h, 35 out of 84 patients (41.2%) and 22 out of 84 patients (26.3%), respectively, needed more sedatives; in the first 24 h and after the first 24 h, 22 out of 84 patients (26.0%) and 18 out of 84 patients (21.4%) needed more analgesics. Conclusion: The safety and effectiveness of dexmedetomidine were similar across the demographic factors in this study. The interindividual variability due to pharmacokinetic parameters can be further studied along with pharmacogenomic factors that may cause the difference in the responses to dexmedetomidine use.